Open circuit characteristics of the compound configuration - Singh A. (My University, 2025)
The expressions previously derived by the author for the resistance parameters of the composite transistors are used to investigate theoretically tho open circuit characteristics of the compound configuration consisting of two-point contact type transistors. It is found that tho system has, in general, a much smaller current gain, voltage gain, input resistance and higher output resistance. The characteristics are greatly modified when the second-point contact type transistor is replaced by a junction type. © 1970 Taylor and Fancis Group, LLC.